A founder noncoding GALT variant interfering with splicing causes galactosemia. Issue 6 (21st August 2020) - Latchman, Kumarie; Brown, Jeanette; Sineni, Claire J.; Ragin‐Dames, Lorrien; Guo, Shengru; Huang, Jingyu; Thorson, Willa; Hacker, Stephanie; Barbouth, Deborah; Tekin, Mustafa; Bademci, Guney
Abstract: Galactosemia is a rare, treatable hereditary disorder of carbohydrate metabolism. We investigated the etiology of decreased GALT enzyme activity in a cohort of newborns referred by the Florida Newborn Screening Program with no detectable GALT variants in diagnostic molecular tests. Six affected individuals from four families with Guatemalan heritage were included. GALT enzyme activity ranged from 20% to 34% of normal. Clinical findings were unremarkable except for speech delay in two children. Via genome sequencing followed by Sanger confirmation we showed that all affected individuals were homozygous for a deep intronic GALT variant, c.1059+390A>G, which segregated as an autosomal recessive trait in all families. The intronic variant disrupts splicing and leads to a premature termination and is associated with a single haplotype flanking GALT, suggesting a founder effect. In conclusion, we present a deep intronic GALT variant leading to a biochemical variant form of galactosemia. This variant remains undiagnosed until it is specifically targeted in molecular testing.